A Rare case report of Oligodontia in the permanent dentition (Bangladesh Journal of Medical Science, 2014)
Oligodontia is a rare congential disorder of dental anomalies that can occur either as an isolated finding or as part of a syndrome. It is defined as agenesis of six or more teeth excluding the third molars. It is commonly seen in permanent than in deciduous dentition. Patients suffering from oligodontia may present with complex problem such as dental and facial disfigurement. Management of those cases generally requires multidisciplinary approach to restore esthetic and function. This paper reports a rare case of oligodontia in an 18 year old adult female patient who has been missing eight permanent teeth excluding the third molars, clinically and radiographically. DOI: http://dx.doi.org/10.3329/bjms.v13i4.16048 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.488-491